(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
This article talks about the uniqueness of the speech of a child with autism syndrome and various speech defects that occur in children with autism syndrome. At the same time, there are recommendations about the most optimal stages of forming communication skills in a non-speaking autistic child.